Crime and Corruption in New Democracies - Moran, J. author. aut Link
IX, 233 p.
Keywords: One of the dark sides to democratization can be crime and corruption. This book looks at the way political liberalization affects these practices in a number of ways whilst also challenging some of the scare stories about democracy. The book also brings the politics of power back into an examination of corruption.